2017
DOI: 10.1097/ccm.0000000000002568
|View full text |Cite
|
Sign up to set email alerts
|

Faster Blood Flow Rate Does Not Improve Circuit Life in Continuous Renal Replacement Therapy: A Randomized Controlled Trial

Abstract: There was no difference in circuit life whether using blood flow rates of 250 or 150 mL/min during continuous renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…In our study, CVVHD at 100 mL/min blood flow was associated with longer circuit survival compared with CVVH at a median blood flow of 200 mL/ min. In addition, Fealy et al [18] found that shorter aPTT and higher platelet counts were associated with earlier crashing of the CRRT circuits, in line with our findings. A comparison of catheters used in this study was the object of a previous paper published by our group [19].…”
Section: Relationship To Previous Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, CVVHD at 100 mL/min blood flow was associated with longer circuit survival compared with CVVH at a median blood flow of 200 mL/ min. In addition, Fealy et al [18] found that shorter aPTT and higher platelet counts were associated with earlier crashing of the CRRT circuits, in line with our findings. A comparison of catheters used in this study was the object of a previous paper published by our group [19].…”
Section: Relationship To Previous Studiessupporting
confidence: 92%
“…It is thus possible that the higher blood flows typically used with CVVH might improve circuit lifespan and compensate for other circuit shortening effects of CVVH. However, more recently, Fealy et al [18] conducted a RCT of 2 different blood flow levels during CVVH and found no effect of blood flow on circuit lifespan. In our study, CVVHD at 100 mL/min blood flow was associated with longer circuit survival compared with CVVH at a median blood flow of 200 mL/ min.…”
Section: Relationship To Previous Studiesmentioning
confidence: 99%
“…The time associated with the opposing treatment on-time is known as the circuit or filter life [1,3,[5][6][7][8][9], and although foundation literature and consensus groups provide definitions and nomencla-Blood Purif 2020;49:490-495 DOI: 10.1159/000505260 ture for CRRT [6,7,10], no specific definition is provided for this key treatment variable. Many studies investigating and reporting CRRT methods for anticoagulation report this data as filter or circuit life (hours), and two recent studies provide a clearer definition in their methods citing high transmembrane pressure, visible clot, and or inability to operate the blood pump and therapy stopping [11,12] as indicators reflecting clotting or clogging (the mechanism). They are associated criteria for ceasing CRRT and the life or cumulative time since the circuit started measured in hours.…”
Section: Introductionmentioning
confidence: 99%
“…Rajajee et al [3] considered acute liver failure patients typically coagulopathic and at risk for intracranial hemorrhage. Fealy et al [4] associated the decreased platelet count (hazards ratio, 1.19; p = 0.03) with a reduced likelihood of circuit clotting repeated events in critically ill adults requiring continuous renal replacement therapy. Muzaffar et al [5] could differentiate among normo coagulant, hypo coagulant, hyper coagulant states by thromboelastography unlike conventional coagulation assay which estimated the platelet count at 153.96±99.16 (×10 ).…”
Section: Discussionmentioning
confidence: 99%